2006
DOI: 10.1007/s10750-006-0061-z
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure and avian communities across a salinity gradient in evaporation ponds of the San Francisco Bay estuary

Abstract: Commercial salt evaporation ponds comprise a large proportion of baylands adjacent to the San Francisco Bay, a highly urbanized estuary. In the past two centuries, more than 79% of the historic tidal wetlands in this estuary have been lost. Resource management agencies have acquired more than 10 000 ha of commercial salt ponds with plans to undertake one of the largest wetland restoration projects in North America. However, these plans have created debate about the ecological importance of salt ponds for migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 21 publications
0
35
0
2
Order By: Relevance
“…These habitat conditions may favour the species, since well-developed meadows of submerged vegetation could provide refuge against predators and abundant food resources for this species (Alcaraz et al, 2008;OlivaPaterna et al, 2009). Furthermore, it has been demonstrated that lower values of salinity in these systems promote high diversity and biomass of macroinvertebrates (Takekawa et al, 2006;López et al, 2010), which are potential prey for A. iberus. In a study on Aphanius fasciatus (Nardo, 1827), Leonardos et al (1996) reported that populations of this species inhabiting lower salinity habitats had higher growth rates and lower values of mortality due mainly to the abundant presence of aquatic macrophytes, which offered abundant food resources and refuge against piscivorous birds.…”
Section: Discussionmentioning
confidence: 99%
“…These habitat conditions may favour the species, since well-developed meadows of submerged vegetation could provide refuge against predators and abundant food resources for this species (Alcaraz et al, 2008;OlivaPaterna et al, 2009). Furthermore, it has been demonstrated that lower values of salinity in these systems promote high diversity and biomass of macroinvertebrates (Takekawa et al, 2006;López et al, 2010), which are potential prey for A. iberus. In a study on Aphanius fasciatus (Nardo, 1827), Leonardos et al (1996) reported that populations of this species inhabiting lower salinity habitats had higher growth rates and lower values of mortality due mainly to the abundant presence of aquatic macrophytes, which offered abundant food resources and refuge against piscivorous birds.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing salinity was found to be correlated with a reduced richness of plant and animal species (5,6) and of microbial community diversity in some cases (7,8). However, this pattern is not consistently observed for all microbial communities (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 88%
“…For example, invertebrate productivity can be affected by vegetation composition and cover, topography and water depth diversity, duration of flooding, and salinity (Severson 1987;Batzer and Resh 1992;Batzer and Wissinger 1996;Takekawa et al 2006;Batzer 2013). However, invertebrate responses to management may be taxonand region-specific, requiring careful research to identify effective strategies (Batzer 2013).…”
Section: Research Needsmentioning
confidence: 99%